Protection from COVID-19 disease in hamsters vaccinated with subunit SARS-CoV-2 S1 mucosal vaccines adjuvanted with different adjuvants - Sui, Yongjun; Andersen, Hanne; Li, Jianping; Hoang, Tanya; Bekele, Yonas; Kar, Swagata; Lewis, Mark G.; Berzofsky, Jay A. (Frontiers in Immunology, 2023)
Adjuvant plays an important role in directing the immune responses induced by vaccines. In previous studies, we have shown that a mucosal SARS-CoV-2 S1 subunit vaccine adjuvanted with a combination of CpG, Poly I:C and IL-15 (named CP15) induced effective mucosal and systemic immunity and conferred nearly sterile protection against SARS-CoV-2 viral replication in macaque models. In this study, we used a hamster model, which mimics the human scenario and reliably exhibits severe SARS-CoV-2 disease similar to hospitalized patients, to investigate the protection efficacy of the vaccines against COVID-19 disease. We compared the weight loss, viral loads (VLs), and clinical observation scores of three different vaccine regimens. All three regimens consisted of priming/boosting with S1 subunit vaccines, but adjuvanted with alum and/or CP15 administrated by either intramuscular (IM) or intranasal (IN) routes: Group 1 was adjuvanted with alum/alum administrated IM/IM; Group 2 was alum-IM/CP15-IN; and Group 3 was CP15-IM/CP15-IN. After challenge with SARS-CoV-2 WA strain, we found that the alum/CP15 group showed best protection against weight loss, while the CP15 group demonstrated best reduction of oral SARS-CoV-2 VLs, suggesting that the protection profiles were different. Sex differences for VL and clinical scores were observed. Humoral immunity was induced but not correlated with protection. Moreover, S1-specific binding antibody titers against beta, omicron BA.1, and BA.2 variants showed 2.6-, 4.9- and 2.8- fold reduction, respectively, compared to the Wuhan strain. Overall, the data suggested that adjuvants in subunit vaccines determine the protection profiles after SARS-CoV-2 infection and that nasal/oral mucosal immunization can protect against systemic COVID-19 disease.